A Modified de novo Insertion Technique for Catheter Replacement in Elderly Hemodialysis Patients: A Single Clinic Retrospective Analysis. Issue 6 (November 2016) - Wang, Lihua; Wei, Fang; Chen, Haiyan; Sun, Guijiang; Yu, Haibo; Jiang, Aili
Purpose: For patients who rely on a tunneled cuffed catheter, replacement or catheter removal is typically necessary. We recently performed a modified de novo insertion technique for catheter replacement in our practice. As the technique has not yet been studied comprehensively, we performed a retrospective study to evaluate the safety and efficacy of de novo placed catheter without delay for catheter replacement in elderly hemodialysis patients. Methods: A retrospective review of 164 elderly patients was conducted during a period of three years. There were 84 patients in study group, as well as 80 patients in a control group, who had catheter replacement by guidewire exchange technique. Clinical follow-up data was collected. Results: All catheters were placed successfully. The mean survival time per catheter was 641 catheter days (study group) and 485 catheter days (control group). The primary patency rates of 30 days were 97.7% (study group) and 90% (control group), respectively, with statistically significant difference (p = 0.04). The incidence of catheter infection was not statistically significantly different in both groups (p = 0.586), but the case of catheter dysfunction was significantly lower in study group compared to control group (p = 0.003). Conclusions: The de novo placed catheter without delay technique for catheter replacement near the pre-existing venotomy site is safe, and boasts similar infection rates with lower dysfunction rates compared to tunneled catheter insertion by guidewire exchange technique.